OPTIMIZATION OF ACYCLOVIR SUSPENSION: FORMULATING DEVELOPMENT USING NA-CMC AND QUALITY CONTROL OF FINISHED PRODUCTS - MUSTARICHIE, RESMI; PRIAMBODO, DRAJAD; RAMDHANI, DANNI; SAPTARINI, NYI MEKAR (International Journal of Applied Pharmaceutics, 2022)
Objective: Acyclovir is widely used as a potent antiviral drug to treat viral infections of herpes and varicella-zoster families. Unfortunately, the drug has a very poor oral bioavailability character (15-30%). The purpose of this study was to develop a formulation of acyclovir suspension with a simple suspension method using Na-CMC (carboxymethylcellulose sodium), and to carry out quality control of the finished product. Methods: The formulation was developed by designing variations in Na-CMC concentration and quality control, including pH, viscosity, dispersibility, storage stability, microscopic measurement, sedimentation volume, and evaluation of acyclovir levels. Quality control is to evaluate the suspension in order to obtain good and stable physicochemical properties of the suspension. Results: Design variations of Na-CMC concentrations of 1.4%, 1.5%, and 1.6% resulted in a homogeneous suspension and easily dispersed perfectly. The three formulas did not have a significant difference in the value of viscosity, permeability, and sedimentation volume, which were not significant. All formulas have pseudoplastic flow properties, with good particle size uniformity in the range of 0–13 µm. The stability of pH during storage time was shown by the formula with 1.5% Na-CMC. Conclusion: The acyclovir suspension with 1.5% Na-CMC concentration was the best compared to the other formulas in terms of stability and physicochemical properties.